1974
DOI: 10.1073/pnas.71.4.1384
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of the Isoenzymes of Human Creatine Phosphokinase

Abstract: Studies of the three human creatine phosphokinase (EC 2.7.3.2) isoenzymes, MM, MB, and BB,show that important differences exist in substrate dependency of the reaction rates. A method was developed to study these properties in which the ATP formed in the reverse reaction was measured by means of firefly luciferase. With substrate conditions at which the isoenzymes showed substantial differences in activity the method could be used for the detection of changes in the-isoenzyme pattern of the' serum of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 17 publications
(10 reference statements)
1
6
0
1
Order By: Relevance
“…Because the rate of formation of ATP from creatine phosphate is greater for CK-MB than for CK-MM (45), the acute increase in CK-MB in skeletal muscle after severe exercise may facilitate the intracellular shuttle of energy, thereby enhancing the repletion of local cellular energy stores (8,38). The large increase in plasma CK-MB activity after the marathon race in the present study is similar to those reported previously (3,28,41,43).…”
Section: Resultssupporting
confidence: 91%
“…Because the rate of formation of ATP from creatine phosphate is greater for CK-MB than for CK-MM (45), the acute increase in CK-MB in skeletal muscle after severe exercise may facilitate the intracellular shuttle of energy, thereby enhancing the repletion of local cellular energy stores (8,38). The large increase in plasma CK-MB activity after the marathon race in the present study is similar to those reported previously (3,28,41,43).…”
Section: Resultssupporting
confidence: 91%
“…Firefly luciferase luminescence has been employed previously for continuous, qualitative measurement of oxidative phosphorylation [16,17], photosynthetic phosphorylation [18,19], and, more recently, a determination of creatine phosphokinase isoenzymes [20]. Such techniques have seen limited application because of the inability to quantitative ATP concentration during the continuous recording.…”
Section: Luminescence and Atp Concentrationmentioning
confidence: 99%
“…The CK activity was measured with a luminescence technique based on the method proposed by Witteveen et al ( 1974) and Lundin (1 978). The prisms from Torpedo electric organ were homogenized in 100 m M Tris, 1 mM EDTA, 5 mM Mg acetate, 2 M mercaptoethanol, pH 8.…”
Section: Activity Of Ckmentioning
confidence: 99%